IMPLEMENTASI KURIKULUM 2013 DALAM KEGIATAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH KEJURUAN NEGERI 13 MALANG - Subhan Adi Santoso; Idzi’ Layyinnati; M.Chotibuddin (Jurnal Pendidikan Islam, 2017)
Abstract: Curriculum 2013 consisting of goals, structure and curriculum, educational calendar and syllabus. Islamic religious education, this time religious teachers should be aware that there are four trends that will be faced by religion and is a challenge for rel igious people as follows: internal diversity, diversity of structural, cultural diversity, criticism of science. The author will choose a location study at Vocational High School 13 Malang, the subject of his research is the principal, vice principal part of the curriculum, Islamic religious education teachers, and students. In this study the authors used three kinds of data collection techniques are methods of observation, interviews, documentation methods. The results of the study as follows: 1. Planning Islamic Religious Education Learning is a teacher before committing learning activities in the classroom should be made syllabus and lesson plans. 2. Implementation of Islamic Religious Education Learning is the implementation phase for the design drawn up plans for teachers. 3. Evaluation of Islamic Religious Education Learning is a measuring instrument to measure the achievement of objectives.